The execution of Minister of Agrarian Affairs Regulation No. 12 of 2017, which concerns the implementation of the Comprehensive Systematic Land Registration (PTSL) in Weragati Village, Majalengka Regency, is currently underway. - Junaedi, Oding; Juliansyah Nugrah, Maulana Fajar; Rahman, Alip (Hukum Responsif, 2024)
The Complete Systematic Land Registration (PTSL) is a thorough procedure of registering all unregistered land parcels in every region of the Republic of Indonesia, inside a single village/sub-district or other administrative unit at the same level, conducted concurrently. The PTSL method is a government project spearheaded by the Ministry of ATR/BPN to cater to the basic needs of the community, such as clothing, food, and shelter. The research methodology used is juridical-empirical, which is a type of qualitative research. This study made use of both primary and secondary legal information. The potential obstacles in executing the Complete Systematic Land Registration (PTSL) program encompass unresolved PPH and BPHTB taxes, absentee land ownership concerns, surplus and neglected land, human resource constraints, insufficient facilities and infrastructure, and challenges in acquiring precise physical and legal data.